I am attempting the following exercise from Annie Liang's excellent lecture notes: enter image description here

I have written an attempted proof (below), but I'm worried about the independence assumption I make. In particular, surely I cannot say that $\mathbb{E}[\sum^n_{i = n'+1} Y_i | \overline{Y}_n) = \mu$?


WTS: $\mathbb{E}[\overline{Y}_{n'} | \overline{Y}_n] = \overline{Y}_n$

$$\begin{align} \overline{Y}_{n'} &= \frac{1}{n'} \sum_{i=1}^{n'} Y_i\\ &= \frac{1}{n'} \bigg[ \sum_{i=1}^{n} Y_i - \sum_{i=n'+1}^{n} Y_i \bigg] \\ &= \frac{1}{n'} \bigg[ n \overline{Y}_n - \sum_{i=n'+1}^{n} Y_i \bigg] \\ &= \frac{n}{n'} \overline{Y}_n - \frac{1}{n'} \bigg[ \sum_{i=n'+1}^{n} Y_i \bigg] \\ &= \overline{Y}_n + \dfrac{n - n'}{n'} \overline{Y}_n - \frac{1}{n'} \sum^n_{i = n'+1} Y_i \\ &= \overline{Y}_n + \dfrac{n - n'}{n'} \sum_{i=1}^n Y_i- \frac{1}{n'} \sum^n_{i = n'+1} Y_i \end{align}$$

I can then take expectations conditional $\overline{Y}_n$, letting $\mathbb{E}(Y_n) = \mu$. Note that independence $\implies \sum^n_{i = n'+1} Y_i = (n - n') \mu$. $$\begin{align} \mathbb{E}[\overline{Y}_{n'} | \overline{Y}_n] &= \overline{Y}_n + \frac{1}{n'}\frac{n-n'}{n} n \mu - \frac{1}{n'} \mu (n - n') \\ &= \overline{Y}_n + \mu \bigg[ \frac{n-n'}{n'} - \frac{n-n'}{n'} \bigg] \\ &= \overline{Y}_n \end{align}$$

  • $\begingroup$ You cannot say $\mathbb{E}\left[\sum\limits^n_{i = n'+1} Y_i \mid \overline{Y}_n\right] = \mu$ for two reasons: the expectation of each term in the sum should be $\overline{Y}_n$ rather than $\mu$; and there are $(n-n')$ such terms rather than $1$. $\endgroup$
    – Henry
    Commented May 17 at 20:31

1 Answer 1


The following fact is key. Since $\bar{Y}_n=n^{-1}\sum_{i=1}^n Y_i$, we can take expectations conditional on $\bar{Y}_n$ and use that $\{Y_i\}$ is an i.i.d. sequence to obtain $$\bar{Y}_n=\mathbb{E}[\bar{Y}_n|\bar{Y}_n]=n^{-1}\sum_{i=1}^n\mathbb{E}[Y_i|\bar{Y}_n]=\mathbb{E}[Y_1|\bar{Y}_n]$$

Using this, we find $$\mathbb{E}\left[\sum_{i=n'+1}^nY_i\Bigg|\bar{Y}_n\right]=\sum_{i=n'+1}^n \mathbb{E}[Y_i|\bar{Y}_n]=(n-n')\mathbb{E}[Y_1|\bar{Y}_n]=(n-n')\bar{Y}_n$$

Therefore, using your expression $$\bar{Y}_{n'}=\bar{Y}_n+\frac{n-n'}{n'}\bar{Y}_n-\frac{1}{n'}\sum_{i=n'+1}^nY_i$$ we can derive $$\begin{align*} \mathbb{E}[\bar{Y}_{n'}|\bar{Y}_n] &=\bar{Y}_n+\frac{n-n'}{n'}\bar{Y}_n -\frac{1}{n'}\mathbb{E}\left[\sum_{i=n'+1}^nY_i\Bigg|\bar{Y}_n\right] \\ &=\bar{Y}_n+\frac{n-n'}{n'}\bar{Y}_n-\frac{n-n'}{n'}\bar{Y}_n \\ &= \bar{Y}_n\end{align*} $$

We could have also gotten this without any manipulation of the sum by noting $$\mathbb{E}[\bar{Y}_{n'}|\bar{Y}_n]=\frac{1}{n'}\sum_{i=1}^{n'}\mathbb{E}[Y_i|\bar{Y}_n]\stackrel{i.i.d.}{=}\mathbb{E}[Y_1|\bar{Y}_n]=\bar{Y}_n$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.